The Virtual Reality Experience and Leisure Experience of Screen Horse Riding Participants: from the ‘Simulation’ point of view by Boudrillard - Jeong Mi, Lim; Soo Woen, Lim; Hyun Ok, Oh (International Journal of Engineering and Technology, 2018)
This study aims to gain depth understanding of the virtual reality experience experienced by screen riding, to analyze in depth and interpret from the perspective of Boudrillard through a subjective and subjective perspective of leisure users. In this study, after learning about the experience of virtual reality symbols built into them through screen riding, the leisure experience of screen riding participants was further identified. The double-checking results are as follows. First, experience in the virtual reality of screen riding can be described as a fusion of virtual reality symbols and experiences. The virtual reality symbols inherent in screen riding are expressed as spatial symbols, behavioral symbols, and contents, and the fusion of experience means a transcendental and a transformative environment. Second, screen riding was a derivative of the study that enabled participants to enter horseback riding more easily and to continue with leisure activities, also to help with posture correction, constipation, diet, and Kegel exercise. thereby enhancing fun and desire for horseback riding. In the study, participants were focusing on subjective feelings arising from the experience of horseback riding, and they stated that the body's sensory stimuli increased the quality of life and felt happy. In this study, the leisure activities are satisfied with the simulacra which can replace reality according to the subjective viewpoint of the leisure experiencer and the reflection of personal circumstances in the virtual reality of screen riding sports which is IT fusion. In the future, It is necessary to study the consumption patterns and the popularity of the emerging virtual reality sports since various virtual reality sports are becoming popular and are being built into the culture of life.Â